Correlation of epididymal protease inhibitor and fibronectin in human semen. - Xiangxiang Zhang; Jianzheng Fang; Bin Xu; Shengli Zhang; Shifeng Su; Zhen Song; Yunfei Deng; Hainan Wang; Dan Zhao; Xiaobing Niu; Zengjun Wang (PLoS ONE, 2013)
OBJECTIVE:Epididymal protease inhibitor (Eppin) was located on the surface of spermatozoa and modulates the liquefaction of human semen. Here, we identify the correlative protein partner of Eppin to explore the molecular mechanism of liquefaction of human semen. METHODS:(1) Human seminal vesicle proteins were transferred on the membrane by Western blotting and separated by 2-D electrophoresis and incubated in recombinant Eppin. The correlative protein was identified by Mass Spectrometry (MS) (2). Western blotting was used to determine the relation of rEppin and rFibronectin(Fn); (3) Co-localization in spermatozoa were detected using immunofluorescence; (4) Correalation of Eppin and Fn was proved by co-immunoprecipitation. RESULTS:Fn was identified as the binding partner of recombinant Eppin by MS. Recombinant of Eppin was made and demonstrated that the Eppin fragment binds the fn 607-1265 fragment. The Eppin-Fn complex presents on the sperm tail and particularly in the midpiece region of human ejaculated spermatozoa. Immunoprecipitation indicated that Eppin in the spermatozoa lysates was complexed with Fn. CONCLUSIONS:Our study demonstrates that Eppin and Fn bind to each other in human semen and on human ejaculated spermatozoa. Eppin-Fn complex may involve in semen coagulation, liquefaction and the survival and preparation of spermatozoa for fertility in the female reproductive tract.